Mesiodens: A clinical and radiographic study in children - S Mukhopadhyay (Wolters Kluwer Medknow Publications, 2011)
Background: A mesiodens is a supernumerary tooth located in the palatal midline between the two maxillary central incisors. The overall prevalence varies between 0.15 and 1.9%. The present study aimed to evaluate the epidemiological characteristics of mesiodens in the pediatric population. Materials and Methods: A longitudinal prospective study was carried out in 7932 children to determine the prevalence of mesiodens. The following data were also recorded: age, sex, shape, sagittal position, orientation, eruption status, number and complications caused by mesiodens. Results: The prevalence of mesiodens in the present study was 0.8%. The sex ratio was 1.78:1, favoring boys. The majority of mesiodens (67.9%) were conical in shape, followed by the supplemental (17.9) and tuberculate (14.1%) types. 71.8% of the mesiodens were palatally placed, 25.6% erupted on the arch and 2.6% were labially positioned. A majority of the mesiodens (62.8%) were vertically aligned. Inverted and horizontal positions were observed in 30.8% and 6.4% of the cases. Most of the mesiodens (53.8%) were impacted, and 14 children had two mesiodens. Most of the mesiodens were associated with complications, and only 26.9% were asymptomatic. Conclusions: The prevalence of mesiodens was 0.8% .Conical shape, palatal position and vertical orientation were common characteristic observations in the study.